Frugal innovation and social transitions in the digital era - Tunio, Muhammad Nawaz 1984-; Memon, Atia Bano 1984- (IGI Global, 2023)
The objective of this book is through its contributed chapters that strive to find out and understand the social value of innovation, frugal innovation, and social innovation in society at local, national, and international levels.